Evaluation of different cropping systems for marginal uplands in Barangay Caticugan, Sta. Rita, Samar - Cagasan, Ulysses A.; Alcober, Ed Allan L.; Gerona, Mark Gil B.; Prado, Gretchen Mae M. (Annals of Tropical Research, 2017)
To help improve the lives of upland farmers in Barangay Caticugan, Sta. Rita, Samar, there is a need to find ways to increase crop yield and income. This study aimed to determine cropping systems that improve crop productivity, increase income and promote cropping systems technology to upland farmers in Barangay Caticugan, Sta Rita, Samar. The experimental units were arranged in Randomized Complete Block Design with three replications. The cropping systems tested were monocropping on corn, peanut and mungbean and intercropping corn + peanut and corn + mungbean. This paper considered only the data for one cropping planted during dryseason. The growth and yield characteristics of all crops under study were not significantly (p<0.05) affected by the cropping systems. Fresh herbage yield (t ha-1) and total yield (t ha-1) in all crops (corn, peanut & mungbean) and harvest index of peanut were significantly affected by the treatments. The significant variations on the said treatments were due to the difference in the plant population of monocultures and the intercrops. On the other hand, corn + mungbean gave a land equivalent ratio (LER) of 1.16, which means that such practice is more productive than growing corn or mungbean as monocrop. Likewise, corn + peanut have an LER value of 1.20 which means corn + peanut intercropping system is more advantageous over monocropping. Economic analysis revealed that monoculture of peanut and mungbean is the most profitable cropping system as it provides a relatively higher yield and net income.